Interleukin 35: Critical regulator of immunity and lymphocyte-mediated diseases. Issue 5 (October 2015) - Egwuagu, Charles E.; Yu, Cheng-Rong; Sun, Lin; Wang, Renxi
Highlights Update on current understanding of the immunebiology of IL-35 and subunits (p35 and Ebi3). IL-35 induces expansion of lymphocytes into regulatory B (135-Breg) and T (iTR35) cells. Autologous i35-Breg is effective therapy for experimental uveitis. IL-35 suppresses experimental autoimmune uveitis and collagen-induced arthritis.